Customer satisfaction at container operation department of Northport (Malaysia) Berhad / Mazlina Samsidi - Samsidi, Mazlina (Faculty of Business and Management, 2006)
The relationship between service quality and customer satisfaction has received considerable academic attention in the past few years. But the nature of the exact relationship between service quality and customer satisfaction is still shrouded with uncertainty. This study attempts to identify which service quality dimension mostly importance for the customer, to identify the level of customer satisfaction and to examine the link between service quality and customer satisfaction by using SERVQUAL Model developed by Parasuraman et.al. A total of 44 companies were selected as a respondent to answer a questionnaire. The results indicate that reliability is an important dimension for port user and most of the customers are not satisfied with tangible dimension. The finding also showed that the two constructs are indeed independent but are closely related, implying that an increase in one is likely to lead to an increase in another.